The sutureless circumcision:a novel surgical innovation - Ray, M. S.; Deepak, B. S. (International Surgery Journal, 2016)
Background: Circumcision is a commonly performed surgical procedure done all over the world for various reasons. There are a number of ways to achieve the same which have been used from ancient times till recent times. Sutureless circumcision is a novel surgical technique which we have used with excellent results, good cosmesis and wound healing. The objective of this study was to bring forward a novel and new innovative method of circumcision. Methods: The sutureless circumcision was performed over 132 patients from 1992 till date with excellent results. Results: The incidences of complications were minimal with excellent wound healing though some cases had self-limiting penile oedema which subsided subsequently. Conclusions: This novel technique has given excellent results and it can be used in countries where there is paucity of funds as it is very economical advocating a newer technique of circumcision without the use of costly tissue adhesive etc. which would bring about a revolution.